2021
DOI: 10.1186/s12885-021-08565-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive potential of Nomogram based on GMWG for patients with hepatocellular carcinoma after radical resection

Abstract: Background Since it’s a challenging task to precisely predict the prognosis of patients with hepatocellular carcinoma (HCC). We developed a nomogram based on a novel indicator GMWG [(Geometric Mean of gamma-glutamyltranspeptidase (GGT) and white blood cell (WBC)] and explored its potential in the prognosis for HCC patients. Methods The patients enrolled in this study were randomly assigned to training and validation cohorts. And we performed the Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 44 Moreover, we compared our nomogram with other similar models for HCC patients published in the previous literature. These models include a nomogram based on NLR (neutrophil to lymphocyte ratio), GMWG (the geometric mean of GGT and white WBC count), and tumor size with a C-index value of 0.70, 45 a prognostic model developed by parameters of Aspartate Transaminase/Alanine Transaminase Ratio and clinical features with a C-index value of 0.680, 46 and a prognostic model constructed by platelet count and clinical features with a C-index value of 0.660. 47 Our model achieved a C-index of 0.712 (95% CI, 0.698–0.726), indicating higher predictive accuracy compared to these previously published models.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Moreover, we compared our nomogram with other similar models for HCC patients published in the previous literature. These models include a nomogram based on NLR (neutrophil to lymphocyte ratio), GMWG (the geometric mean of GGT and white WBC count), and tumor size with a C-index value of 0.70, 45 a prognostic model developed by parameters of Aspartate Transaminase/Alanine Transaminase Ratio and clinical features with a C-index value of 0.680, 46 and a prognostic model constructed by platelet count and clinical features with a C-index value of 0.660. 47 Our model achieved a C-index of 0.712 (95% CI, 0.698–0.726), indicating higher predictive accuracy compared to these previously published models.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 309 patients with OSCC, a high platelet count, high neutrophil count and low lymphocyte count were found to be associated with reduced overall survival (OS) and disease-free survival (DFS) (13). Some studies have also indicated that an increased pretreatment neutrophil-to-lymphocyte ratio (NLR) is associated with poor outcomes in hepatocellular carcinoma, colorectal cancer, endometrial cancer, and gastric cancer (14)(15)(16)(17). However, few studies have reported the prognostic values of the ratios of immune-inflammatory cells, such as the NLR, lymphocyte-to-monocyte ratio (LMR), neutrophil-to-white blood cell ratio (NWR), and lymphocyte-to-white blood cell ratio (LWR), especially in patients with OSCC.…”
Section: Introductionmentioning
confidence: 99%